Remote robot-assisted day surgery for liver: A report of 2 cases - Zhenqi Li; Xiuping Zhang; Zhaohai Wang; Yuyao Song; Lichao Pan; Rong Liu (Intelligent Surgery)
Objective: To report for the first time the experience of hepatectomy through remote robot-assisted day surgery and comment on the safety and feasibility of this surgical mode. Method: Two patients underwent remote robot-assisted day surgery for liver conditions at the First Medical Center of the Chinese People's Liberation Army (PLA) General Hospital on October 17, 2024. The perioperative management process and conditions of these two patients were described. Results: Both patients underwent successful remote robot-assisted liver day surgery. The total length of surgery was 121 min and 102 min for the two patients, with master-slave control times of 66 min and 41 min, respectively. The surgery and intraoperative imaging were smooth, with a maximum delay of 56 ​ms and a packet loss rate of 0%. The volume of intraoperative estimated blood loss was 20 mL for both patients. Surgery was completed successfully and both patients were discharged within 24 h. Conclusion: This study preliminarily confirms the safety and efficacy of remote robot-assisted day surgery for liver diseases, providing a new clinical practice direction for the future development of liver surgery.